136 Quantitative and qualitative analysis of interferon stimulated genesMX2, OAS1, and ISG15 for detection of pregnancy in cattle. (28th November 2020) - DeCarlo, Andrea N; Parrish, Joseph; Long, Nathan; Pratt, Scott
Abstract: Pregnancy in cattle can be determined using transrectal ultrasonography or by detection of pregnancy associated glycoproteins present in maternal circulation begging at approximately d 28 of gestation; however, the majority of pregnancy loss occurs prior to this date. Interferon stimulated genes (ISG) have been observed to be upregulated in pregnant cattle and measurable at d 18 of gestation. The objective of this study was to assess ISG expression as an indicator of pregnancy at d 18 post-insemination. A 7-d Co Synch and CIDR estrous synchronization protocol was utilized on cows of varying age and parity (n = 80) and insemination to a single sire performed 60 to 66 h following removal of the CIDR. On d 0 and d 18 post-insemination, blood was collected via jugular venipuncture for isolation of total RNA by PAXgene Blood RNA kit (PreAnalytiX, Hombrechtikon, Switzerland). Pregnancy detection was performed on d 30 of gestation by transrectal ultrasonography. Differences in ISG expression between d 0 and d 18 samples in both pregnant (n = 10) and open (n = 10) cows, according to d 30 ultrasound, were assessed. Primers for ISGs (MX2, OAS1, and ISG15) and housekeeping, cyclophilin were generated for use in end-point PCR and qRT-PCR. Data for qRT-PCR were normalized to cyclophilin expression. Analysis of variance and pair-wise student's t-test among LSMeans were performed with fixed effects for pregnancy status, day, and their interactions. End-point products in all ISGs, regardless of day or pregnancy status, were observed. Expression of MX2 and ISG15 were upregulated in open cows and in d 0 samples (P < 0.05). Expression of OAS1 was increased in open cows (P = 0.001). These data disagree with previous findings in which ISGs were upregulated in pregnant animals, and indicate expression of these ISGs may not be good indicators for pregnancy.